2017
DOI: 10.1111/ene.13323
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pain and motor and non‐motor symptoms in Parkinson's disease

Abstract: We confirm that pain in PD is more frequent in women and in subjects with medical conditions predisposing to painful symptoms. Moreover, this strengthens the association between pain and motor severity measures and NMS domains, particularly sleep and mood disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
(34 reference statements)
3
24
1
Order By: Relevance
“…Most neurologists treat patients with chronic pain, but few have received any training in this area, underscoring a clear educational need. Nevertheless, pain is frequently under‐recognized and often not reported by patients and, because it can have such an impact on daily quality of life, it is incumbent on clinicians to investigate its presence and assess it in relation to the whole spectrum of non‐motor symptoms . Clinicians should try to understand what type of pain the patient is suffering because the underlying mechanisms and treatment options vary.…”
Section: Management Of Pain In Clinical Practicementioning
confidence: 99%
“…Most neurologists treat patients with chronic pain, but few have received any training in this area, underscoring a clear educational need. Nevertheless, pain is frequently under‐recognized and often not reported by patients and, because it can have such an impact on daily quality of life, it is incumbent on clinicians to investigate its presence and assess it in relation to the whole spectrum of non‐motor symptoms . Clinicians should try to understand what type of pain the patient is suffering because the underlying mechanisms and treatment options vary.…”
Section: Management Of Pain In Clinical Practicementioning
confidence: 99%
“…In general population, sleep disturbances and pain are frequent co-morbidities. There is evidence from experimental and longitudinal studies that pain and sleep interact in a bidirectional manner and negatively affect each other.11 In PD, studies have shown that sleep disturbances are a risk factor for pain and vice versa 10,1216…”
Section: Introductionmentioning
confidence: 99%
“…In line with the abovementioned link between network integration and cognition, cognitive decline in PD has been associated with decreased functional connectivity (Olde Dubbelink et al, 2014 ; Amboni et al, 2015 ) or deviant coupling between subnetworks of the brain (Putcha et al, 2016 ). Another non-motor symptom is pain (Broen et al, 2012 ; Choi et al, 2017 ), a symptom that is present in about two thirds of patients and has been associated with sleep and mood disturbances, as well as severity of motor symptoms (Broen et al, 2012 ; Defazio et al, 2017 ). Pain in PD has been linked to a functional disconnection between the hippocampus and nucleus accumbens (Polli et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%